EFEKTIVITAS METODE BELAJAR MANDIRI DALAMMENGEMBANGKAN KREATIVITAS BERPIKIR SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SD NEGERI KEDUNGWARAS MODO LAMONGAN - Siti Maunah (Akademika, 2017)
Has become a self-learning potential of children born with underdeveloped due to formal-traditional pendidikian system which emphasizes the role of the teacher (teacher center). But with the development of the times, the education system turns into a student center point is more emphasis on the activity and creativity of the students to develop their identity or ability. From the above background, appears formulation of the problem to be discussed: first how the application of self-learning method on subjects PAI (Islamic Education) in Elementary School Kedungwaras districts Modo Lamongan, both how the development of creative thinking of students on subjects PAI (Religious Education Islam) in elementary school districts Kedungwaras Modo Lamongan, third how the effectiveness of self-learning method in developing the creative thinking of students on subjects PAI (Islamic Education) in elementary school districts Kedungwaras Modo Lamongan. Lots of methods applied in the world of learning, related to curriculum diterapkanya 2013 which has general purpose is to improve the competence manifested in intelligence, knowledge, personality, character, and skills to live independently and to follow further education. This research is a field research (field research) with a qualitative descriptive approach and to obtain data on the effectiveness of self-learning method in developing the creative thinking of students on subjects PAI (Islamic Education) in Elementary School Kedungwaras districts Modo Lamongan, after the collected data analysis research the percentage technique, then study dideskriptifkan to the conclusion by using the method of observation, documentation, interviews and questionnaires. The study concluded that the self-learning method is quite effective at all in developing creative thinking of students on subjects PAI (Islamic Education) in elementary school districts Kedungwaras Modo Lamongan with indicators as follows; the percentage calculation above may take the average value of 69.05%, which is between 40-70%, and 50-82% student response was very positive in the category enough. So many students are more responsible, the students were able to argue in accordance with their own ideas, students are more confident, students more easily solve the problem, happy to discuss, more and more skilled active.